The Propionyl Ester of Lovastatin Decreases the Levels of Very Long Chain Fatty Acids in Fibroblasts Derived from Patients with X‐linked Adrenoleukodystrophy - Song, Jiho; Hur, Hye‐Jin; Lee, Jung Wuk; Wenas, Michelle A.; Chung, Shin Hyuck; Kim, Dong Wook; Jang, Jiho; Min, Kyung Hoon (Bulletin of the Korean Chemical Society, 2018)
KCI Citation Count: 0